The Natives Learned How To Live Healthy: European Waste Management In Semarang (1916-1930) - Naila, Silvi Nihlatin; Witasari, Nina (Journal of Indonesian History, 2024)
Entering the 20th century, modernization became the central theme in the Dutch East Indies, especially in the cities where most Europeans lived. Semarang, as a municipality, is also trying to modernize; the government's main focus is to introduce a clean lifestyle and protect the European-style environment. The European view is used as the standard of cleanliness in Semarang, even though the native people have their own way of handling waste, such as community service work every week. In contrast, Europeans are used to a particular waste management team formed by the government. This research will explain how the waste management service was formed in Semarang and the government's efforts to educate the native community. This research uses historical research methods, namely heuristics (source collection), criticism (verification of sources obtained), interpretation (interpretation), and historiography (writing). The results show that the modernization promoted by the government cannot be separated from the proposal of several Europeans to bring the native community along in the process. Therefore, a waste management service and educational curriculum were formed. However, the success of government intervention to change lifestyles has not been completely successful because in the end many people still throw rubbish carelessly.